Characterization of Seasonal Variations in Responsiveness of Pituitary Gland to Different Doses of Gonadotropin Releasing Hormone in Buffalo Cows - RUDRAIAH, MEDHAMURTHY; Jyotsna, U.R.; Kunal, B.S.; Killivalavan, A.; Sudeshna, T.; Ravindra, J.P. (Journal of Buffalo Science, 2012)
In tropical countries such as India, it has been observed that a number of buffalo cows experience seasonal anestrous during summer months. This might be due to seasonal changes in responsiveness of pituitary gland to gonadotropin releasing hormone (GnRH) and/or decreased hypothalamic GnRH release. Attempts were made to characterize the responsiveness of pituitary gland to a range of doses (0.1, 1, 3, 10 and 33 µg) of GnRH in terms of LH and progesterone (P4) secretions during summer (April-May) and rainy (September-November) months. As a part of these studies, a radioimmunoassay method for estimation of circulating LH in buffalo cows was standardized. During summer months, it was observed that in the presence of low circulating P4 levels the minimum dose of GnRH required for eliciting a significant increase in circulating LH levels was 10 μg/animal that corresponded to a dose of 28 ng/kg BW. However, during rainy months, administration of the same dose of GnRH failed to elicit a response suggesting that the pituitary gland is not responsive to low doses of exogenous GnRH. On the other hand, buffalo cows receiving a dose of 100 µg of GnRH during rainy months elicited a surge-like increase in circulating LH that peaked at 2 h and the increase in LH concentrations lasted for nearly 6 h post GnRH treatment. The results appear to suggest that during summer months the pituitary gland function is not affected, but there may be lowered hypothalamic GnRH input to the pituitary gland.